Antagonistic Test of Endophytic Bacteria Against Fusarium oxysporum f.sp. cepae Causes of Moler Disease on Shallots - Wihayyu, Afri; Resti, Zurai; Sulyanti, Eri; Darnetty, Darnetty; Khairul, Ujang (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2024)
Fusarium oxysporum f.sp. cepae (FOCe) is a pathogenic fungus causing moler disease in shallots. One method of controlling this disease is by using endophytic bacteria. Endophytic bacteria are bacteria that live in plant tissues without causing disease symptoms. This research aims to obtain the most effective endophytic bacteria in inhibiting the growth of the pathogenic fungus FOCe. The study employs a Completely Randomized Design (CRD) consisting of 8 treatments with 3 replications each. The treatments include Bacillus sp. HI, Bacillus sp. SJI, Bacillus cereus P14, Bacillus cereus Se07, Bacillus subtilis, Serratia marcescens JB1E3, Serratia marcescens ULG1E4, and control. Tests conducted include the antibiosis test of endophytic bacterial cells using the dual culture method and the secondary metabolite test using media poisoning method. The observed parameters include inhibition zone, effectiveness of secondary metabolites, fresh weight, and dry weight of the FOCe fungus. All endophytic bacteria were capable of inhibiting the growth of FOCe. The most effective endophytic bacteria in inhibiting the growth of FOCe were found to be Serratia marcescens ULG1E4 and Serratia marcescens JB1E3. In the antibiosis test of endophytic bacterial cells, Serratia marcescens ULG1E4 exhibited an inhibition zone of 64.44%, while Serratia marcescens JB1E3 showed an inhibition zone of 61.11%. In the secondary metabolite compound test, the effectiveness values for Serratia marcescens ULG1E4 and Serratia marcescens JB1E3 were 95.31% and 95.03%, respectively.